2019
DOI: 10.1016/j.ajhg.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation Studies for Single Circulating Trophoblast Genetic Testing as a Form of Noninvasive Prenatal Diagnosis

Abstract: It has long been appreciated that genetic analysis of fetal or trophoblast cells in maternal blood could revolutionize prenatal diagnosis. We implemented a protocol for single circulating trophoblast (SCT) testing using positive selection by magnetic-activated cell sorting and single-cell low-coverage whole-genome sequencing to detect fetal aneuploidies and copy-number variants (CNVs) at $1 Mb resolution. In 95 validation cases, we identified on average 0.20 putative trophoblasts/mL, of which 55% were of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
96
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(105 citation statements)
references
References 20 publications
(36 reference statements)
3
96
2
Order By: Relevance
“…Since cell-free DNA (cfDNA) was detected in the peripheral blood of pregnant women by Lo YM in 1997 [5], and with the rapid development of high-throughput sequencing technology in recent years, noninvasive prenatal testing (NIPT) has been gradually developed to analyze cfDNA and deduce the presence of fetal chromosomal abnormalities through amplification, high-throughput sequencing technology, and bioinformatics processing [6]. Compared with serological screening, sonographic screening, and other traditional interventional prenatal diagnosis methods, NIPT is noninvasive, has high sensitivity, and can avoid the risk of abortion, infection, or injury caused by invasive interventional operations [7]. Therefore, NIPT is rapidly being employed to detect the fetal chromosome aneuploidies of T21, T18, T13, and SCAs around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Since cell-free DNA (cfDNA) was detected in the peripheral blood of pregnant women by Lo YM in 1997 [5], and with the rapid development of high-throughput sequencing technology in recent years, noninvasive prenatal testing (NIPT) has been gradually developed to analyze cfDNA and deduce the presence of fetal chromosomal abnormalities through amplification, high-throughput sequencing technology, and bioinformatics processing [6]. Compared with serological screening, sonographic screening, and other traditional interventional prenatal diagnosis methods, NIPT is noninvasive, has high sensitivity, and can avoid the risk of abortion, infection, or injury caused by invasive interventional operations [7]. Therefore, NIPT is rapidly being employed to detect the fetal chromosome aneuploidies of T21, T18, T13, and SCAs around the world.…”
Section: Introductionmentioning
confidence: 99%
“…However, those studies have reported variable results and it is difficult to conclude if there is a definite association between recovered fetal cell numbers and gestational age. [18][19][20][21] Furthermore, there are only two previously reported studies in which the influence of BMI on the number of fetal cells was explored in a small number of samples (91 and 85 samples). 18,22 Here, we present the results of our study by evaluating how the number of fetal cells recovered varies with maternal BMI and gestational age of the pregnancy on a larger number of samples than previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal characteristics and obstetrical history including BMI and gestational age at the time of blood collection were recorded. The protocol used in this study was validated and published by Vossaert et al18 Briefly, after an initial red…”
mentioning
confidence: 99%
“…This partly explains the current inability to propose a routine NIPD protocol based on CFTC analysis for monogenic diseases caused by point mutations. It also emphasizes the importance of having not a single diagnostic cell but multiple diagnostic cells, recently recommended by Vossaert L et al (2019) for CNV analysis 30 . Indeed, the analysis of each single CFTC is critical because first, the quality of these cells can vary substantially since some cells are in an apoptotic state involving genome-wide degradation.…”
Section: Discussionmentioning
confidence: 95%